Is dialysis water a safe component for hemodialysis treatment in São Paulo State, Brazil? - Ellen Gameiro Hilinski; Adriana Aparecida Buzzo Almodovar; Fernando Pontes de Lima e Silva; Terezinha de Jesus Andreoli Pinto; Adriana Bugno (Universidade de São Paulo, 2020)
Failure on the water treatment poses hemodialysis patients at risk of injury and death. Identifying if the patients are exposed to water quality related microbiological risks is an important objective to reduce the mortality for chronic renal patients and is the main issue of this study. We evaluated the microbiological water quality used by 205 dialysis services in São Paulo State, Brazil between 2010 to 2016. The study included heterotrophic bacteria count, total coliforms research, and bacterial endotoxin determination in 1366 dialysis water samples. The number of unsatisfactory clinics for at least one microbiological parameter decreased 16.0% between 2010 to 2015 but increased 57.2% in 2016. In 2010, the most frequent unsatisfactory parameter was related to heterotrophic bacteria count (54.8%) followed by endotoxin determination (45.2%). However, in 2013 an opposite situation was observed: endotoxin determination as the parameter of the higher incidence of nonconformities. Total coliform was verified at a lower frequency. We highlighted the importance of regular monitoring of dialysis water quality to prevent infections caused by dialytic procedures and to ensure that the water is a safe component of the treatment.